(untitled) (LACCEI, 2024)
Downstream erosion of catchment structures is a natural and very common process, most of it is due to the dragging of sediments, erosion, and foreign elements contained in its channel. Therefore, it is necessary to apply protection methods to mitigate the failure process during its useful life of the structure, therefore, the present work focuses on proposing protection methods to reduce the depth of erosion using a gabion with different gravel diameters in the erosion pool downstream of the hydraulic structure. , built on burdensome arene beds. A brief comparison of this dimension was made by applying protection methods to the model and without them, in this way it was possible to evaluate the increase or decrease of the variable mentioned above. The research is based on physical modeling and based on the principles of hydraulic similarity (model – prototype). The results for the Remonta II diversion dam infer that increases in the depth, length and erosion time dimensions are related to gravel diameter and maximum flow rates.